An indoor contaminant sensor placement toolbox for critical infrastructure buildings - Eliades, Demetrios G.; Michaelides, Michalis P.; Christodoulou, Marinos; Kyriakou, Marios; Panayiotou, Christos G.; Polycarpou, Marios M. (My University, 2013)
In this work, we address the problem of airborne contaminant sensor placement in high-risk buildings where critical infrastructures are managed and operated, making them possible locations for terrorist attacks (such as governmental buildings and ministries, utilities, airports and hospitals). A new software is presented based on the "Matlab-CONTAM Toolbox" and the CONTAM multi-zone simulation software, to construct multiple scenarios of contamination events and to solve the multi-objective sensor placement problem for minimizing the average and maximum impact risk with respect to the contaminant mass inhaled impact metric. The use of the software is demonstrated in a case-study using the Holmes's House benchmark. The Toolbox is released under an open-source license at https://github.com/KIOS-Research/ matlab-contam-toolbox.
Keywords: Contamination; Sensor Placement; Critical Infrastructure Protection; High-Risk Buildings; MATLAB-CONTAM Toolbox